2021
DOI: 10.5194/acp-2021-547
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling secondary organic aerosol formation from volatile chemical products

Abstract: Abstract. Volatile chemical products (VCPs) are commonly-used consumer and industrial items that are an important source of anthropogenic emissions. Organic compounds from VCPs evaporate on atmospherically relevant time scales and include many species that are secondary organic aerosol (SOA) precursors. However, the chemistry leading to SOA, particularly that of intermediate volatility organic compounds (IVOCs), has not been fully represented in regional-scale models such as the Community Multiscale Air Qualit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
(94 reference statements)
0
9
0
Order By: Relevance
“…In current and previous public, operational versions of CMAQ, lower-volatility, gas-phase anthropogenic ROC emissions were not represented in the chemical mechanism . As a result, much of the VCP mass (∼30%), often dominated by IVOCs, was not considered for SOA or radical chemistry. Recent work , introduced several new chemical components to the AERO7 module within CMAQ to alleviate this issue with a focus on alkane-like IVOCs, oxygenated IVOCs, SVOCs, and siloxanes, and modeled Los Angeles air quality during the 2010 California Nexus of Air Quality and Climate Change (CalNex) campaign …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In current and previous public, operational versions of CMAQ, lower-volatility, gas-phase anthropogenic ROC emissions were not represented in the chemical mechanism . As a result, much of the VCP mass (∼30%), often dominated by IVOCs, was not considered for SOA or radical chemistry. Recent work , introduced several new chemical components to the AERO7 module within CMAQ to alleviate this issue with a focus on alkane-like IVOCs, oxygenated IVOCs, SVOCs, and siloxanes, and modeled Los Angeles air quality during the 2010 California Nexus of Air Quality and Climate Change (CalNex) campaign …”
Section: Methodsmentioning
confidence: 99%
“…Here, we incorporate a new VCP inventory 9 into the Community Multiscale Air Quality (CMAQ) model with VCP-specific chemistry updates 21 to better represent VCP emissions and subsequent air quality impacts throughout the contiguous United States. These updates include the representation of secondary air pollutant formation pathways for alkane-like IVOCs, oxygenated IVOCs, and siloxanes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Wu et al (2019) constructed an inventory of S/IVOCs for the Pearl River Delta (PRD) region in China and conducted a simulation using the Weather Research and Forecasting model with Chemistry (WRF-Chem) that led to an increase of 161 % in SOA predictions. Emissions of S/IVOCs from mobile sources and IVOCs from volatile chemical products were also parameterized in models to represent SOA formation (Jathar et al, 2017;Lu et al, 2020;Pennington et al, 2021). Although the significant role of potential emission sources in OA formation has been demonstrated, the underestimation of SOA by current air quality models has not been completely resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Their emissions can be larger than those from usual sources, such as motor vehicles (Coggon et al, 2021). Laboratory, modeling, and field studies for VCPs have been conducted to assess their potential to affect ambient OA and ozone formation in urban and suburban locations (McDonald et al, 2018;Khare et al, 2018;Stockwell et al, 2021;Seltzer et al, 2021;Gkatzelis et al, 2021;Milani et al, 2021;Pennington et al, 2021;Coggon et al, 2021). The contribution of VCPs to ambient OA is not fully understood and only limited modeling studies have been reported (Mohr et al, 2015;Vlachou et al, 2018;Pennington et al, 2021;Qin et al, 2021;Seltzer et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory, modeling, and field studies for VCPs have been conducted to assess their potential to affect ambient OA and ozone formation in urban and suburban locations (McDonald et al, 2018;Khare et al, 2018;Stockwell et al, 2021;Seltzer et al, 2021;Gkatzelis et al, 2021;Milani et al, 2021;Pennington et al, 2021;Coggon et al, 2021). The contribution of VCPs to ambient OA is not fully understood and only limited modeling studies have been reported (Mohr et al, 2015;Vlachou et al, 2018;Pennington et al, 2021;Qin et al, 2021;Seltzer et al, 2021). Additionally, few experimental and chamber studies of VCPs have been conducted with limited characterization of aerosol products Johnston, 2016, 2017;Harrison and Well, 2012;Charan et al, 2020Charan et al, , 2021Humes et al, 2022).…”
Section: Introductionmentioning
confidence: 99%